2019
DOI: 10.1152/ajpcell.00341.2018
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress, autophagy and airway ion transport

Abstract: Mucociliary clearance is critically important in protecting the airways from infection and from the harmful effects of smoke and various inspired substances known to induce oxidative stress and persistent inflammation. An essential feature of the clearance mechanism involves regulation of the periciliary liquid layer on the surface of the airway epithelium, which is necessary for normal ciliary beating and maintenance of mucus hydration. The underlying ion transport processes associated with airway surface hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 249 publications
(305 reference statements)
1
16
0
Order By: Relevance
“…Autophagy, as a catabolic process, is considered to protect the cells against various factors of stress and is aimed at recycling cytoplasmic components and damaged organelles caused by diverse stress [ 41 , 42 ]. A lot of evidence reveals oxidative stress-mediated occurrence of autophagy in diverse kinds of cells [ 43 ], including ARPE-19 cells. It is reported that autophagy plays a positive role in promoting cell survival and anti-apoptosis [ 44 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, as a catabolic process, is considered to protect the cells against various factors of stress and is aimed at recycling cytoplasmic components and damaged organelles caused by diverse stress [ 41 , 42 ]. A lot of evidence reveals oxidative stress-mediated occurrence of autophagy in diverse kinds of cells [ 43 ], including ARPE-19 cells. It is reported that autophagy plays a positive role in promoting cell survival and anti-apoptosis [ 44 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mucociliary clearance is critically important in protecting the airways. But overwhelming of mucus may be result in acute and chronic effects dysfunction of mucociliary clearance, which is known to caused Oxidative stress (O'Grady, 2019). Current asthma therapies fail to target airway remodeling that correlates with asthma severity driving disease progression that ultimately leads to loss of lung function (McAlinden et al, 2019).…”
Section: Mechanisms and Regulation Of Asthma Progression Involved In Autophagymentioning
confidence: 99%
“…Moreover, other ion channels, including CFTR, Ca 2+ -activated Cl − channel (CaCC) and Slc26A9, affect Cl − release [ 47 ]. Additionally, oxidative stress is known to have acute and chronic effects on airway ion transport [ 48 ].…”
Section: The Biological Characteristics Of Mucinsmentioning
confidence: 99%